Interoperability in healthcare - Miranda, Miguel (2010)
Hospital Information Systems need to communicate in order to share information and to make it available at anyplace at whatever time. Indeed, these systems have to go along with the fundamentals of ubiquity and quality-of-care, being embedded in some forms of intelligent mechanisms in order to be useful for medical, clinical and administrative sta . In fact, to ful ll this goal, the information available must be judge in terms of its quality, acquired via a process of quanti cation of the extensions of the predicates that make their realm, i.e., speaking for a high degree of con dence on it on the part of the users. Admittedly, centralized systems are not a solution, they speak for themselves. The answer, once one must be able to exchange and make use of information, is interoperability.